All those Nations : Cultural Encounters within and with the Near East - Vanstiphout, H.L.J. (Comers/ICOG Communications, 2000)
This collection of studies treats the theme of cultural (and other) confrontations between different groups (ethnic, or linguistic, or political, or religious...) within the Middle East, but also in some contributions, the types of confrontation between the West and the Middle East.